1993
DOI: 10.1007/bf01352219
|View full text |Cite
|
Sign up to set email alerts
|

Polyvinyl butyral as a dispersant for barium titanate in a non-aqueous suspension

Abstract: Polyvinyl butyral (PVB) was used as a dispersant for BaTi03 in a toluene-methanol system and its efficiency was evaluated by measuring the zeta potential and by a rheological study of the suspension. Addition of only 1.6 vol % Iow-mo ecu ar-weight (50 000) PVB is effective in making a well-dispersed suspension. But a lower concentration (0.6 vol %) of high-molecularweight (200 000) PVB is necessary to stabilize the suspension due to the longer chain length of the polymer, which enhances steric stabilization. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
1

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 5 publications
0
39
0
1
Order By: Relevance
“…As the concentration increased, the rheological behavior became dilatant, which is characteristic of highly loaded suspensions with a high repulsive force between particles. 19 The suspension having a 25.1 vol.% of solids presented pseudoplastic behavior, indicating poor dispersion. In other words, PVB is not efficient in dispersing concentrated suspensions (> 21 vol.%).…”
Section: Viscosity Measurementsmentioning
confidence: 97%
See 3 more Smart Citations
“…As the concentration increased, the rheological behavior became dilatant, which is characteristic of highly loaded suspensions with a high repulsive force between particles. 19 The suspension having a 25.1 vol.% of solids presented pseudoplastic behavior, indicating poor dispersion. In other words, PVB is not efficient in dispersing concentrated suspensions (> 21 vol.%).…”
Section: Viscosity Measurementsmentioning
confidence: 97%
“…19 What part of the copolymer is adsorbed on the particle's surface is still a controversial issue. While it is usually assumed that adsorption is due to PVB, Parker and Sacks studied copolymers containing different amounts of PVA and demonstrated that adsorption on the alumina increases as the amount of PVA increases.…”
Section: Viscosity Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…En el colado en banda, se prefiere utilizar una mezcla de dos disolventes a trabajar con un líquido puro, porque la solubilidad de los polímeros es generalmente mayor en un sistema mixto optimizado que en cualquier disolvente 75 . Las características de los disolventes a elegir dependerán de la naturaleza de los aditivos empleados para estabilizar la suspensión y para conferir la resistencia mecánica adecuada a la pieza colada en crudo.…”
Section: Optimización De Las Suspensiones De Circonaunclassified